BIM short course for construction industry professionals = Curso corto en BIM dirigido a los profesionales de la industria de la construcción - Sampaio, Alcínia Zita; Lozano-Diez, Rafael V. (Advances in Building Education, 2020)
The Building Information Modelling (BIM) methodology is currently the main work platform in the construction industry, and all sectors have been enhancing its applicability. The demonstration of the benefits registered in the development of various activities motivates the great interest. affirmed by architects, engineers and managers, in knowing its concept and the scope of its applicability. Recently, higher education technical schools have been following this interest, introducing changes into their curricular programs and also offering short courses to construction industry professionals. In recent years, the Department of Civil Engineering of the University of Lisbon, Portugal, has organized courses concerning BIM with the aim of meeting the professionals’ needs. To this end, the most recent short course offered to the technical community covered aspects, from the parametric modelling concept to the analysis of the interoperability capacity of the software. The text presents the course program - concept, practice, structures and construction - and the assessment of the degree of satisfaction of participants, based on their pre-course expectations and interest they had in attending the course. It can be concluded that the school and the industry should continue to collaborate in order to reinforce the efficiency of the construction sector.ResumenLa metodología Building Information Modelling (BIM) es actualmente la principal plataforma de trabajo en la industria de la construcción, y todos los sectores han estado potenciando su aplicabilidad. La demostración de los beneficios registrados en el desarrollo de diversas actividades motiva el gran interés, verificado por arquitectos, ingenieros y gestores, por conocer su concepto y el alcance de su aplicabilidad. Las escuelas técnicas han estado siguiendo este interés, introduciendo cambios en sus programas curriculares y ofreciendo también cursos cortos a profesionales de la industria de la construcción. El Departamento de Ingeniería Civil de la Universidad de Lisboa, Portugal, ha estado organizando cursos sobre la cuestión BIM, en una perspectiva de lograr las necesidades de los profesionales. En este caso, el curso corto más reciente ofrecido a la comunidad técnica abarca varios aspectos, desde el concepto de modelado paramétrico hasta el análisis de la capacidad de interoperabilidad. El texto presenta el programa del curso (concepto, práctica, estructuras y construcción) y la evaluación del grado de satisfacción de los participantes, confrontado con sus expectativas e interés en asistir al curso. La escuela y la industria han estado colaborando para potenciar la eficiencia del sector de la construcción.